Bottom-up fabrication of nanohole arrays loaded with gold nanoparticles: extraordinary plasmonic sensors - Weiler, Markus; Quint, Stefan B.; Klenk, Simon; Pacholski, Claudia (Chemical communications, 2014)
A chemical route to periodic hole arrays in gold films whose holes are loaded with single gold nanoparticles is presented, paving the road to mass production of highly sensitive plasmonic sensors on large areas.